RUNOFF PRODUCTION AND EROSION PROCESSES ON A DEHESA IN WESTERN SPAIN* - Ceballos, Antonio; Cerdà, A.; Schnabel, Susanne (Geographical Review, 2010)
Runoff generation and soil erosion were investigated at the Guadalperal6n ex- perimental watershed (western Spain), within the land-use system known as dehesa, or open, managed evergreen forests. Season and type of surface were found to control runoff and soil- loss rates. Five soil units were selected as representative of surface types found in the study area: hillslope grass, bottom grass, tree cover, sheep trails, and shrub cover. Measurements were made in various conditions with simulated rainfall to gain an idea of the annual varia- tion in runoff and soil loss. Important seasonal differences were noted due to surface cover and moisture content of soil, but erosion rates were determined primarily by runoff. Surfaces covered with grass and shrubs always showed less erosion; surfaces covered with holm oaks showed higher runoff rates, due to the hydrophobic character of the soils. Concentrations of runoff sediment during the siniulations confirmed that erosion rates at the study site de- pended directly on the sediment available on the soil surface
Keywords: Dehesa; erosion; land use; rainfall simulation; runoff; Spain